2009
DOI: 10.1139/f09-066
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced growth limitation of juvenile fishes in an estuarine nursery: assessment of small-scale temporal dynamics using RNA:DNA

Abstract: The ratio of RNA to DNA (RNA:DNA) in white muscle tissue of juvenile summer flounder (Paralichthys dentatus) and weakfish (Cynoscion regalis) was used as a proxy for recent growth rate in an estuarine nursery. Variability in RNA:DNA was examined relative to temporal changes in temperature and dissolved oxygen (DO). Initial laboratory experiments indicated (i) a strong positive relationship between RNA:DNA and growth rate, (ii) a rapid response of RNA:DNA to changes in feeding, and (iii) no effect of hypoxia on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 47 publications
2
55
0
1
Order By: Relevance
“…The occurrence of hypoxia in coastal and estuarine environments, and the impacts of hypoxia on estuarine organisms, have been well documented in recent years (Wannamaker and Rice 2000;Bell and Eggleston 2005;Goodman and Campbell 2007;Thomas et al 2007;Stierhoff et al 2009). Coastal hypoxia generally occurs in warm months, and the duration of hypoxic events can vary from months, weeks or days to hours or minutes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of hypoxia in coastal and estuarine environments, and the impacts of hypoxia on estuarine organisms, have been well documented in recent years (Wannamaker and Rice 2000;Bell and Eggleston 2005;Goodman and Campbell 2007;Thomas et al 2007;Stierhoff et al 2009). Coastal hypoxia generally occurs in warm months, and the duration of hypoxic events can vary from months, weeks or days to hours or minutes.…”
Section: Introductionmentioning
confidence: 99%
“…However, estuarine species often have a relatively high tolerance to hypoxia, although remaining in such sub-optimal conditions can result in decreased growth (Coiro et al 2000;McNatt and Rice 2004;Stierhoff et al 2006Stierhoff et al , 2009 and reproductive impairment (Thomas et al 2007;Landry et al 2007;Brouwer et al 2007;Brown-Peterson et al 2008). Furthermore, exposure to hypoxia can have profound physiological consequences on fish and invertebrates, such as alterations in systemic and molecular control mechanisms of oxygen transport (Cochran and Burnett 1996;Mangum 1997;Terwilliger 1998;McMahon 2001;Paul et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed the major energy allocation to osmoregulation causes a decrease in growth in the estuary of the Saloum (Panfili et al, 2006). Certain factors such as increased salinity may also induce a reduction in the growth of some estuarine species (Panfili et al, 2004;Stierhoff et al, 2009).…”
Section: Linear Growthmentioning
confidence: 99%
“…Scientific studies have found evidence that hypoxia can affect different fish species in various ways such growth and mortality (for example, Peterson et al, 2000;Miller et al, 2002;Stierhoff et al, 2009;Thomas et al, 2007). While the biological effects of hypoxia on marine species are relatively well studied, the body of work that focuses on the economic consequences of hypoxia is still quite limited.…”
Section: Introductionmentioning
confidence: 99%